Surface Functionalization of Gold Nanoparticles for Antiviral Medicines by Simulating the Surface Structure of Host Cells - Yujiro Naruse, (Journal of Basic & Applied Sciences, 2015)
Surface functionalized gold nanoparticles that mimic the surfaces of host cells are proposed for antiviral medicines and the strategic design is theoretically described. As for the interaction between the gold nanoparticles and the viruses, the former acts as the adhesive balls for viruses. This will lead to gathering viruses and forming clusters or chains of them, bringing about four-stage antiviral mechanisms. The mechanisms are the interference against budding, reduction of diffusion velocity, inhibition of entry into host cells and the damage to RNA/DNA by X-ray exposure.